Forage production systems in upland agriculture of Jratunseluna watershed - Bambang R Purwadiputra (Jurnal Ilmu Ternak dan Veteriner, 2003)
Study on forage potency at upland area of Jratunseluna watershed was conducted in three different agroecosystems. The locations represent deep soil area (volcanic) and shallow soil area (sediment) and three climate zones, namely zone B-2, C-2 and C-3. Data on forage production and food crops by-product were collected every month in a year. The result showed that there was different forage production between the deep soil and the shallow soil area. The forage production was also influenced by climate zone. The forage balance at each location shows that data collected once in a month was more meaningful on determination of surplus or deficit of forages compare to the one time data collection only. On the forage production, in dry matter as well as TDN, any single animal in volcanic area and B-3 climate zone got more forages compare to other location. On the other hand ruminants in sediment area with C-3 climate zone consumed forages below the demand line. In the sediment area, the number of ruminant depended on forage planted, but in volcanic area did not.   Key words: Forages, potency, volcanic soil, sediment soil